PRINSIP HUKUM DALAM TATA KELOLA RUMAH SAKIT - Erikkson Sitohang (Yuridika, 2014)
Health is a part of human right and one of the elements of well-being that should be realized in accordance with the ideals of the nation of Indonesia as stipulated in Pancasila and the Constitution of the Republic of Indonesia Year 1945. As the implementing regulations contained in Law No. 36 of 2009 on Health, in Article 1 point 1 is determined “Health is a state of health, both physically, mentally, spiritually and socially to enable more people to live socially and economically productive”. Thus, health is a part that should be pursued to achieve the welfare of the nation. One of the efforts to achieve should be manifested in the provision of health care facilities.Keywords: health, hospital, health services.